2013
DOI: 10.1097/mcg.0b013e31828a37c0
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Hepatitis C Treatment Clinical Practice Patterns Using the Newly Approved Protease Inhibitors

Abstract: Goals To describe current HCV treatment practices in the United States and identify physician characteristics associated with the use of first generation DAAs. Background Hepatitis C virus (HCV) treatment practice patterns have not been assessed after the introduction of direct-acting antivirals (DAA), which are now considered standard of care for most HCV genotype 1 patients. Study We sampled nationally representative physicians treating HCV patients with DAAs through a web-based survey. Stepwise multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Although the use of these first DAAs was significantly limited by serious toxicities and drug-drug interactions with relatively poor outcomes among transplant patients, their introduction may have brought optimism to the field about agents in the pipeline or may have reflected a lag between the excitement about the first DAAs and the reporting of adverse outcomes. A survey of transplant physicians found that although 48% of providers were using these first-generation DAAs (protease inhibitors), 22% were going to wait for improved therapies before treating posttransplant, indicating awareness of future therapies and increasing comfort in use of DAAs in HCV-positive liver transplant recipients (24). Long-term shifts in access to liver transplantation among all deceased donor liver transplantation (DDLT) recipients could also partially explain the increase we observed among HCV-positive recipients if declines in access have been leading to increased use of these marginal organs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of these first DAAs was significantly limited by serious toxicities and drug-drug interactions with relatively poor outcomes among transplant patients, their introduction may have brought optimism to the field about agents in the pipeline or may have reflected a lag between the excitement about the first DAAs and the reporting of adverse outcomes. A survey of transplant physicians found that although 48% of providers were using these first-generation DAAs (protease inhibitors), 22% were going to wait for improved therapies before treating posttransplant, indicating awareness of future therapies and increasing comfort in use of DAAs in HCV-positive liver transplant recipients (24). Long-term shifts in access to liver transplantation among all deceased donor liver transplantation (DDLT) recipients could also partially explain the increase we observed among HCV-positive recipients if declines in access have been leading to increased use of these marginal organs.…”
Section: Discussionmentioning
confidence: 99%
“…While the use of these first DAAs was significantly limited by serious toxicities and drug-druginteractions with relatively poor outcomes among transplant patients, their introduction may have brought optimism to the field about agents in the pipeline, or may have reflected a lag between the excitement about the first DAAs and the reporting of adverse outcomes. A survey of transplant physicians found that while 48% of providers were using these first generation DAAs (protease inhibitors), 22% were going to wait for improved therapies before treating post-transplant, indicating awareness of future therapies and increasing comfort in use of DAAs in HCV+ liver transplant recipients (24). Long term shifts in access to liver transplantation among all DDLT recipients could also partially explain the increase we observed among HCV+ recipients if declines in access have been leading to increased use of these marginal organs.…”
Section: Discussionmentioning
confidence: 99%